Influence of the Configuration of Vacuum Spark-gap Electrodes on their Erosion; The 4th International Forum on Strategic Technology (IFOST 2009), Ho Chi Minh City, Vietnam, October 21-23, 2009 - Lavrinovich V. A. (2009, 2009)
В фонде НТБ ТПУ отсутствует